2012
DOI: 10.1371/journal.pbio.1001238
|View full text |Cite
|
Sign up to set email alerts
|

USP8 Promotes Smoothened Signaling by Preventing Its Ubiquitination and Changing Its Subcellular Localization

Abstract: Hedgehog regulates the activity of its signal transducer Smoothened by enhancing its interaction with the deubiquitinase USP8, thereby promoting Smoothened translocation to the cell surface and so enhancing Hh signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
190
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(202 citation statements)
references
References 50 publications
9
190
1
Order By: Relevance
“…One contributing factor to such defective EGFR trafficking is that USP8 controls the stability of ESCRT-0 components, Hrs and STAM in cells and in conditional knockout mice (185,219). However, for Frizzled receptor (Fz) and Smoothened (Smo), key components of Wingless (Wnt) and Hedgehog signaling pathways, respectively, USP8 plays a negative regulatory role with regard to receptor degradation more akin to that originally proposed for AMSH (153,180,281).…”
Section: B Escrt Dubsmentioning
confidence: 99%
“…One contributing factor to such defective EGFR trafficking is that USP8 controls the stability of ESCRT-0 components, Hrs and STAM in cells and in conditional knockout mice (185,219). However, for Frizzled receptor (Fz) and Smoothened (Smo), key components of Wingless (Wnt) and Hedgehog signaling pathways, respectively, USP8 plays a negative regulatory role with regard to receptor degradation more akin to that originally proposed for AMSH (153,180,281).…”
Section: B Escrt Dubsmentioning
confidence: 99%
“…SMO is regulated by the transmembrane protein Patched (PTC; Nakano et al, 1989), which acts as both an SMO antagonist and an HH coreceptor. Studies in flies show that in the absence of signal, PTC promotes SMO internalization and targeting to the lysosome for degradation (Fan et al, 2013;Li et al, 2012;Xia et al, 2012). These effects are blocked by HH, leading to accumulation of a hyperphosphorylated form of SMO at the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Ubpy in Drosophila development is equally controversial. It was suggested that the Hedgehog (Hh) signaling activator Smoothened (Smo) is subject to Ubpy control (Li et al, 2012;Xia et al, 2012). However, Mukai et al (Mukai et al, 2010) found that Smo abundance is unchanged when Ubpy is depleted.…”
Section: Introductionmentioning
confidence: 99%
“…Hrs mutants lacking the FYVE motif and PSAP domain, respectively, were generated by PCR. Wild-type (WT) and catalytically dead (CS) HA-Ubpy plasmids were gifts of Dr Jianhang Jia (Xia et al, 2012). Myc-Ub plasmid was provided by Dr Shunsuke Ishii (Dai et al, 2003).…”
mentioning
confidence: 99%